(x²+4x-4)(x²+4x+1)=6 решите

0 голосов
69 просмотров

(x²+4x-4)(x²+4x+1)=6 решите


Алгебра (17 баллов) | 69 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Замена x^2+4x-4=t
тогда
x^2+4x+1=(x^2+4x-4)+5=t+5
Уравнение перепишется в виде
t(t+5)=6
t^2+5t-6=0
(t+6)(t-1)=0
t_1=-6
t_2=1

---возвращаемся к замене
первый случай
t_1=-6
x^2+4x-4=-6
x^2+4x-4+6=0
x^2+4x+2=0
D=4^2-4*2*1=16-8=8=4*2=2^2*2
x_{1,2}=\frac{-4^+_-2\sqrt{2}}{2*1}=-2^+_-\sqrt{2}
Второй случай
t_2=1
x^2+4x-4=1
x^2+4x-4-1=0
x^2+4x-5=0
(x+5)(x-1)=0
x_3=-5
x_4=1
все найденные четыре корня - решение

(409k баллов)